Comparative analysis of design/build and design/bid/build project delivery systems in Lebanon - Hadi Abou Chakra; Amina Ashi (Journal of Industrial Engineering International, 2019)
Design/bid/build and design/build are two principal project delivery systems used worldwide. The performance of each project may differ with the type of procurement system used. This study has two aims: firstly, to assess and compare the performance of design/bid/build and design/build projects in Lebanon; secondly, to compare the results with the performance of equivalent systems in the Far East and the USA, in order to identify the similarities between Lebanon and these countries. Seven performance indicators were identified in terms of cost, time, quality, communication, risk and safety to evaluate the performance of 102 residential buildings and tower projects completed in Lebanon. Means and medians of these performance indicators were compared to identify which delivery system performs better regarding each indicator. The results presented in this study show some agreements between different performance indicators when applied to principal project delivery systems in the selected countries.
Keywords: 650; Construction management; Project management; Procurement systems; Project delivery systems; Design/bid/build; Design/build